Association between neutrophil-to-lymphocyte ratio and all-cause and cardiovascular mortality among adults with cancer from NHANES 2005-2018: a retrospective cohort study - Li, Gangping; Fu, Yuewen; Zhang, Di (Frontiers in Oncology, 2025)
BackgroundEvidence on the association between the neutrophil-to-lymphocyte ratio (NLR) and all-cause and cardiovascular disease (CVD) mortality in adults with cancer is limited.AimsThis study aimed to examine the relationship between NLR and all-cause and CVD mortality in adults with cancer.MethodsA retrospective cohort study included 2,639 cancer patients in the U.S. from the NHANES dataset (2005-2018), collecting demographic, laboratory, and mortality data. Multivariable Cox regression analysis, subgroup analysis and restricted cubic spline analyses assessed the associations between NLR and mortality outcomes.ResultsDuring a median follow-up of 77 months, 713 (27.0%) deaths occurred, including 149 (5.6%) from CVD. Multivariable Cox regression analysis revealed that a high NLR, treated as a continuous variable, was significantly correlated with increased all-cause mortality (HR, 1.09; 95% CI, 1.05-1.12; p < 0.001) and CVD mortality (HR, 1.12; 95% CI, 1.05-1.19; p < 0.001). Meanwhile, when evaluating NLR as a categorical variable, the adjusted hazard ratios (HR) for NLR and all-cause mortality in quartiles Q2 (1.6-2.2), Q3 (2.2-3), and Q4 (>3) were 1.06 (95% CI: 0.83-1.34, p = 0.062), 1.12 (95% CI: 0.89-1.42, p = 0.334), and 1.30 (95% CI: 1.04-1.63, p = 0.021), respectively, when compared with individuals in the lower quartile Q1 (≤1.6). In terms of CVD mortality, the adjusted HR values for NLR in Q2, Q3, and Q4 were 0.92 (95% CI: 0.50-1.69, p = 0.062), 1.24 (95% CI: 0.71-12.19, p = 0.334), and 1.76 (95% CI: 1.04-2.97, p = 0.034), respectively, compared to those in the lower NLR quartile Q1 (≤1.6). Subgroup analysis showed similar patterns (all p-values for interaction > 0.05). Kaplan-Meier analysis indicated lower survival rates for individuals with higher NLR, and RCS analysis suggested a positive linear relationship between NLR and all-cause and CVD mortality.ConclusionElevated NLR is linked to higher all-cause and CVD mortality risks among adults with cancer.